Aberrant resting-state connectivity of auditory, ventral attention/salience and default-mode networks in adults with attention deficit hyperactivity disorder - Blomberg, Rina; Signoret, Carine; Danielsson, Henrik; Perini, Irene; Rönnberg, Jerker; Capusan, Andrea Johansson (Frontiers in Neuroscience, 2022)
Numerous resting-state studies on attention deficit hyperactivity disorder (ADHD) have reported aberrant functional connectivity (FC) between the default-mode network (DMN) and the ventral attention/salience network (VA/SN). This finding has commonly been interpreted as an index of poorer DMN regulation associated with symptoms of mind wandering in ADHD literature. However, a competing perspective suggests that dysfunctional organization of the DMN and VA/SN may additionally index increased sensitivity to the external environment. The goal of the current study was to test this latter perspective in relation to auditory distraction by investigating whether ADHD-adults exhibit aberrant FC between DMN, VA/SN and auditory networks. 12 mins of resting-state fMRI data was collected from two adult groups: ADHD (n=17) and controls (n=17); from which the FC between predefined regions comprising the DMN, VA/SN and auditory networks were analyzed. A weaker anticorrelation between the VA/SN and DMN was observed in ADHD. DMN and VA/SN hubs also exhibited aberrant FC with the auditory network in ADHD. Additionally, participants who displayed a stronger anticorrelation between the VA/SN and auditory network at rest, also performed better on a cognitively demanding behavioral task that involved ignoring a distracting auditory stimulus. Results are consistent with the hypothesis that auditory distraction in ADHD is linked to aberrant interactions between DMN, VA/SN and auditory systems. Our findings support models that implicate dysfunctional organization of the DMN and VA/SN in the disorder and encourage more research into sensory interactions with these major networks.